Voluntary intake of dry matter and performance of Nellore cows and their Nellore and crossbred Simental × Nellore calves - Vargas Junior, Fernando Miranda de; Wechsler, Francisco Stefano [UNESP]; Rossi, Patrícia; Oliveira, Marcus Vinicius Morais de; Schmidt, Patrick (Sociedade Brasileira de Zootecnia, 2011)
This study aimed to investigate the influence of calf genetic group on the performance of Nellore lactating cows. The variables studied included milk ingestion, pasture intake, calf weight gain and cow body weight. A total of 13 Nellore calves and 8 crossbred Simental × Nellore calves were used, all born from Nellore mothers. During the experimental period of 210 days, calves were weighted at birth and at 30-day intervals, whereas cows were weighed every 14 days. Milk intake was estimated using the weigh-suckle-weigh method. Pasture intake was determined 6, 12, and 24 weeks after birth by using chromic oxide as an external marker and indigestible acid detergent fiber as an internal marker. Average weight of crossbred calves was 10.1 kg and their milk intake was 0.42 kg higher than in purebred calves. There was no difference, however, in pasture intake between genetic groups. In Nellore cows, body weight and pasture consumption (9.2 kg of DM/cow/day) were not influenced by calf heterosis.
Keywords: crossing; grazing; milk; weight gain